Uni-form of the uniform as skin - Molina Winkler, Amanda (2023)
The objective of this essay was to reflect on the use of the school uniform and its subjective implications on the students. A questioning of the main arguments in favor of its use was carried out, emphasizing on the perspective of a uniform as a tool of false inclusion that is used on the basis of reducing differences, also of its use as a possible impediment to the expression of diversity – which is one of the constitutive elements in the construction of one’s identity- and the self-exploration that can occur through the choice of clothing. Through the discussion built around the school uniform, an attempted to carry out a metaphorical analysis of the educational system itself, inviting one to wonder if educational centers are the place to promote a uni-form.